2015
DOI: 10.1016/j.rxeng.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic neoplasms: Interpreting lung findings in chest computed tomography

Abstract: Lung disease is very common in patients with hematologic neoplasms and varies in function of the underlying disease and its treatment. Lung involvement is associated with high morbidity and mortality, so it requires early appropriate treatment. Chest computed tomography (CT) and the analysis of biologic specimens are the first line diagnostic tools in these patients, and sometimes invasive methods are necessary. Interpreting the images requires an analysis of the clinical context, which is often complex. Start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Consistent with the studies by Ahmad et al, Choi et al, and Bugdaci et al, pneumonia was the most common pulmonary manifestation in these patients (3,4,12). Calvillo Batllés et al also found infection to be the most common cause of pulmonary involvement in patients with hematologic neoplasms (16). Nema et al also showed that bacterial and fungal pneumonia were the main causes of lung lesions in patients with hematologic malignancies, whereas bacterial pneumonia and tuberculosis were the main causes in patients without hematologic malignancy (17).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with the studies by Ahmad et al, Choi et al, and Bugdaci et al, pneumonia was the most common pulmonary manifestation in these patients (3,4,12). Calvillo Batllés et al also found infection to be the most common cause of pulmonary involvement in patients with hematologic neoplasms (16). Nema et al also showed that bacterial and fungal pneumonia were the main causes of lung lesions in patients with hematologic malignancies, whereas bacterial pneumonia and tuberculosis were the main causes in patients without hematologic malignancy (17).…”
Section: Discussionsupporting
confidence: 85%
“…a Considering the combination of clinical and paraclinical data, with the results of the CT scan cies in our study (16). In the study conducted by Kosichkina et al, the bacterial source was considered the most com-mon cause of pneumonia, which was significantly associated with the GGO pattern (13).…”
Section: Alveolar Hemorrhage 2 (1)mentioning
confidence: 72%
“…chest X-ray) in all subjects, with the exclusion of echocardiograms. 6 Statistical significance for heterogeneity and subgroup tests was defined as a p-value of <0.05. Reporting bias was explored by visual inspection of funnel plots, when at least 10 studies for a specific frequency measure were available.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…According to Chenjin Ge et al, the most frequent symptoms in patients with VAR fistulas were chest pain and dyspnoea [67]. We found that of the 13 CAF cases reported in the literature, five patients presented with angina [6,24,35,42,55], three with chest discomfort [25,36,37] and three with dyspnoea [25,28,46], whereas two were asymptomatic [10,31].…”
Section: Symptomsmentioning
confidence: 75%
“…Probably, the pressure gradient, which is responsible for the VAR dilation, is the precipitating factor for the formation of VAR aneurysms. The present review includes 13 VAR aneurysm cases, three solitary [26,41,49] and 10 in concurrence with CAFs [10,22,25,28,31,[35][36][37]46,55]. With respect to the study cohort, 43% of the women (p = 0.011) presented with an aneurysm, compared to 14% of the men.…”
Section: Symptomsmentioning
confidence: 99%